Efektifitas Pembelajaran Dengan Pendekatan Tatap Muka di Era Society 5.0 pada As’adiyah Islamic School Kelurahan Sidodadi Wonomulyo Polewali Mandar - Nabilawati, Hijrah; Harianto, Salam; Makduani, Rivai; Rahayu, Muji; Nawawi, Haris; Hasanuddin (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2025)
The aim of the research is to find out whether the face-to-face method is still effective in the learning process at Asadiyah Islamic School, Sidodadi sub-district, Wonmulyo district. The research is qualitative research by conducting observations, interviews and documentation using data analysis techniques: data reduction, data display, conclusion drawing verification. The results of the research are that the face-to-face learning method is still effectively implemented at the Asadiyah Islamic School with the level of use of the face-to-face method reaching (90 percent) with the consideration of building student morals. Face-to-face interaction is very effective, while the use of other methods such as the use of information technology is only as a tool.